Continuous procedure of stochastic approximation in a semi-Markov medium - Chabanyuk, Ya. M. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
Using the Lyapunov function for an averaged system, we establish conditions for the convergence of the procedure of stochastic approximation$$du(t)=a(t)[C(u(t),x(t))dt+σ(u(t))dw(t)]$$in a random semi-Markov medium described by an ergodic semi-Markov process $x(t)$.